Rates of rehospitalisation in the first 2 years among preterm infants discharged from the NICU of a tertiary children hospital in Vietnam: a follow-up study. Issue 10 (5th October 2020) - Do, Chuong Huu Thieu; Børresen, Malene Landbo; Pedersen, Freddy Karup; Geskus, Ronald Bertus; Kruse, Alexandra Yasmin
Abstract : Objectives: To describe the characteristics of rehospitalisation in Vietnamese preterm infants and to examine the time-to-first-readmission between two gestational age (GA) groups (extremely/very preterm (EVP) vs moderate/late preterm (MLP)); and further to compare rehospitalisation rates according to GA and corrected age (CA), and to examine the association between potential risk factors and rehospitalisation rates. Design and setting: A cohort study to follow up preterm infants discharged from a neonatal intensive care unit (NICU) of a tertiary children's hospital in Vietnam. Participants: All preterm newborns admitted to the NICU from July 2013 to September 2014. Main outcomes: Rates, durations and causes of hospital admission during the first 2 years. Results: Of 294 preterm infants admitted to NICU (all outborn, GA ranged from 26 to 36 weeks), 255 were discharged alive, and 211 (83%) NICU graduates were followed up at least once during the first 2 years CA, of whom 56% were hospital readmitted. The median (IQR) of hospital stay was 7 (6–10) days. Respiratory diseases were the major cause (70%). Compared with MLP infants, EVP infants had a higher risk of first rehospitalisation within the first 6 months of age (p=0.01). However, the difference in risk declined thereafter and was similar from 20 months of age. There was an interaction in rehospitalisation rates between GA and CA. Longer duration of neonatal respiratory support and having older siblings were associated with higher rehospitalisation rates. Lower rates of rehospitalisation were seen in infants with higher cognitive and motor scores (not statistically significant in cognitive scores). Conclusions: Hospital readmission of Vietnamese preterm infants discharged from NICU was frequent during their first 2 years, mainly due to respiratory diseases. Scale-up of follow-up programmes for preterm infants is needed in low-income and middle-income countries and attempts to prevent respiratory diseases should be considered.